1988
DOI: 10.1148/radiology.168.2.3393662
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse panbronchiolitis: evaluation with high-resolution CT.

Abstract: High-resolution computed tomography (CT) was performed in 20 patients with diffuse panbronchiolitis. Images of abnormal peripheral lung were classified into four types: small nodules around the end of bronchovascular branchings (CT type I), small nodules in the centrilobular area connected with small branching linear opacities (CT type II), nodules accompanied by ring-shaped or small ductal opacities connected to proximal bronchovascular bundles (CT type III), large cystic opacities accompanied by dilated prox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
1

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 0 publications
1
46
0
1
Order By: Relevance
“…The presence of disseminated, ill-defined small rounded opacities, as well as centrilobular nodules, were generally observed and probably reflected bronchiolar inflammation in the DPB patients (Hamma et al 1983;Akira et al 1988;Nishimura et al 1992 (Jacobsen et al 1986). The use of thin-section CT is superior to chest radiography for the detection of bronchiectasis or mucus plugging (Naidich et al 1982;Grenier et al 1986).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of disseminated, ill-defined small rounded opacities, as well as centrilobular nodules, were generally observed and probably reflected bronchiolar inflammation in the DPB patients (Hamma et al 1983;Akira et al 1988;Nishimura et al 1992 (Jacobsen et al 1986). The use of thin-section CT is superior to chest radiography for the detection of bronchiectasis or mucus plugging (Naidich et al 1982;Grenier et al 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Bhalla et al (1991) have found that thinsection computed tomography (CT) is useful for the evaluation of bronchiectasis and mucus plugging in patients with CF. In patients with DPB, comparative studies using CT and radiographic classifications have demonstrated that the clinical and pathologic stages of the disease correlate well with the radiographic findings (Akira et al 1988). However, no scoring system exists for objectively evaluating the extent and progression of airway disease in patients with DPB.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the disease progresses, the inflammatory changes extend to the proximal airways and inflammation due to bacterial infection is superimposed. In the advanced stage, secondary ectasia of proximal terminal bronchioles (bronchiolectasis) is observed and in the final stage further bronchiectasis occurs (1,2). Elastase released from the inflammatory cells is related to the pathogenesis of lung diseases such as cystic fibrosis (3) and emphysema (4), causing degradation of various types of lung tissue components.…”
Section: Introductionmentioning
confidence: 99%
“…As diffuse panbronchiolitis advances, secondary ectasia of proximal terminal bronchioles (bronchioloec tasis) and further bronchiectasis develop (1,2). Dif fuse panbronchiolitis is often complicated by persistent bacterial infection, and often infected with Pseudomonas aeruginosa in the advanced stages (1) like severe bron chiectasis.…”
Section: Introductionmentioning
confidence: 99%